Management control of intangibles - Martins, Júlio Paulo da Silva (2008)
This paper analyzes the importance of management control on the intangible elements considering its contribution for value creation. Some intangible evaluation models and methodologies are discussed, taking into consideration their utility. A new methodological framework that considers the objectives of management control as well as its applicability is presented.